Modeling of a heavy-lift airship carrying a payload by a cable-driven parallel manipulator. (31st July 2019) - Abdallah, Fida Ben; Azouz, Naoufel; Beji, Lotfi; Abichou, Azgal
In this article, we present a preliminary analysis of a heavy-lift airship carrying a payload through a cable-driven parallel robot. With unlimited access to isolated locations around the globe, heavy-lift airship enables affordable and safe delivery of heavy cargo thanks to its vertical takeoff and landing capabilities. By considering the airship and the cable-driven parallel robot as a combined system, the kinematic and dynamic models are developed. The choice of the proposed decentralized control structure is justified by the weak coupling of the two subsystems (i.e. airship and cable-driven parallel robot) which makes it possible to control the above two subsystems independently. A robust sliding mode control, capable of auto-piloting and controlling the airship, is developed. Furthermore, an inverse dynamic controller is applied to the cable-driven parallel robot in order to ensure loading and unloading phase. The feature of the proposed control system is that the coupled dynamics between the airship and the cable-driven parallel robot are explicitly incorporated into control system design, without any simplifying assumption. Numerical simulation results are presented and a stability analysis is provided to confirm the accuracy of our derivations.